Developing Early Childhood Self-Protection Skills Through Role-Playing: Insights from Bandura’s, Vygotsky’s, and Bronfenbrenner’s Theoretical Perspectives - Mutiara Magta; Asep Supena; Sri Indah Pujiastuti (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
Ensuring children’s growth and development within the school environment is critical to helping them develop self-protection skills. The purpose of this study is to describe how role-playing activities can develop self-protection skills in early childhood based on an analysis of three developmental theories: Bandura’s social cognitive theory, Vygotsky’s sociocultural theory, and Bronfenbrenner’s ecological theory. This study employed a qualitative research method, with data collected through observation during role-playing activities. Observations were conducted in two kindergartens in Indonesia, each of which implemented micro and macro types of role-playing. The observational data obtained through documentation and field notes were analyzed using the Miles and Huberman framework, involving the collection, reduction, and presentation of data in accordance with the thematic patterns of the three developmental theories. The results of the analysis of these three theories indicate that role-playing—whether at the micro or macro level—provides children with opportunities to practice self-protection skills through observation, imitation, scaffolding, and social support. Teachers need to incorporate role-playing as a targeted and collaborative learning strategy that involves both the school and family contexts to ensure that children’s protective skills develop optimally.